2022
DOI: 10.1038/s41598-022-19567-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of mortality and early tracheostomy in patients with COVID-19: a retrospective analysis

Abstract: COVID-19 adds to the complexity of optimal timing for tracheostomy. Over the course of this pandemic, and expanded knowledge of the disease, many centers have changed their operating procedures and performed an early tracheostomy. We studied the data on early and delayed tracheostomy regarding patient outcome such as mortality. We performed a retrospective analysis of all tracheostomies at our institution in patients diagnosed with COVID-19 from March 2020 to June 2021. Time from intubation to tracheostomy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
2
0
1
Order By: Relevance
“…We also found a lower incidence of tracheostomy in the second wave. This is in line with earlier research showing that early tracheostomy does not improve patient outcome [ 27 , 28 ]. This analysis showed a shorter duration of ventilation and a shorter length of hospital and ICU stay in survivors in the second wave.…”
Section: Discussionsupporting
confidence: 92%
“…We also found a lower incidence of tracheostomy in the second wave. This is in line with earlier research showing that early tracheostomy does not improve patient outcome [ 27 , 28 ]. This analysis showed a shorter duration of ventilation and a shorter length of hospital and ICU stay in survivors in the second wave.…”
Section: Discussionsupporting
confidence: 92%
“…15 Flinspach et al published a study in September 2022 that included 117 patients from March 2020 to June 2021 and reported that early tracheostomy was associated with significant increase in mortality. 16 They also noted that the timing of tracheostomy became earlier as the pandemic progressed and more studies 12 confirmed the risk of viral transmission to HCW was less than previously thought and as resources became more easily available. A smaller study involving 47 patients by Battaglini et al in August 2022 reported that timing did not really affect patient outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies revealed that early percutaneous dilatational tracheostomy was safe and could optimize clinical course of patients as well as distribution of critical care resources [ 45 50 ]. However, two recent studies investigating patients with COVID-19 reported an increased mortality in patients undergoing ET (< 10d after intubation; < 21d after intubation) [ 51 , 52 ]. In summary, whether patients with COVID-19 could get clinical benefits by performing early tracheostomy is still controversial, which need more investigations to figure out.…”
Section: Discussionmentioning
confidence: 99%